Bacteriohopanepolyols in tropical soils and sediments from the Congo River catchment area. (December 2015) - Spencer-Jones, Charlotte L.; Wagner, Thomas; Dinga, Bienvenu J.; Schefuß, Enno; Mann, Paul J.; Poulsen, John R.; Spencer, Robert G.M.; Wabakanghanzi, Jose N.; Talbot, Helen M.
Highlights: Biohopanoid composition of tropical Congo soils and wetlands investigated. High concentrations of methane oxidation biomarkers in wetlands. Tropical soils and wetland sediments have low soil marker BHPs (< 20%). Relative abundance variation smaller in tropical soils than temperate/Arctic soils. Abstract: The Congo River basin drains the second largest area of tropical rainforest in the world, including a large proportion of pristine wetlands. We present the bacteriohopanepolyol (BHP) inventory of a suite of tropical soils and, from comparison with published data, propose some initial ideas on BHP distribution controls. Strong taxonomic controls on BHP production are evident in wetland sediments. Dominant within the suite were 35-aminobacteriohopane-31, 32, 33, 34-tetrol (aminotetrol) and 35-aminobacteriohopane-30, 31, 32, 33, 34-pentol (aminopentol), indicating aerobic methanotrophy. A narrow range and low mean relative abundance of 30-(5′-adenosyl)hopane (adenosylhopane) and related compounds, collectively termed "soil marker" BHPs, were observed in Congo soils (mean 17%, range 7.9–36% of total BHPs, n = 22) compared with literature data from temperate surface soils and Arctic surface soils (mean 36%, range 0–66% of total BHPs, n = 28) suggesting a greater rate of conversion of these BHP precursors to other structures.